Chendol Enterprise / Rjuan Afify B Abd Raup... [et al.] - Abd Raup, Rjuan Afify; Abd Lasim, Nuruzaline; Otoi, Sunira; Kasil, Nor Hafiz; Adnan, Nurul Aizie Adnan (Faculty of Hotel And Tourism Management, 2009)
Chendol Enterprise will be operating at Kampung Darau Laut, Kota Kinabalu. Our target market is generally to all types of consumers. We are expecting our business will run successfully and effectively and efficiently operation. Our competitors will be KK More Enterprise and CZC Bubble Tea Supplier Sdn. Bhd. In short, we hope that our business will grow and will take place in people's hearts and lead the market share.